Zinc phosphate salt-based composite pigment loaded with nano slow-release agent and preparation method of zinc phosphate salt-based composite pigment
By loading nano corrosion inhibitors on zinc phosphate-based pigments in three-dimensional spatial structures to form composite pigments, the problem of structural defects in aqueous epoxy coatings is solved, and the self-repair and corrosion resistance of the coating are improved.
Patent Information
- Application Number
- CN202411745503.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
After the existing zinc-ammonium phosphate pigment is doped in aqueous epoxy coatings, structural defects such as pinholes, microcracks and hollows still exist, resulting in damage to the anticorrosion performance of the coating and affecting its service life.
By loading nanocorrosion inhibitors on the zinc phosphate-based pigment in the three-dimensional spatial structure, a zinc phosphate-based composite pigment with nanocorrosion inhibitors is formed, and the release and migration of sustained-release ions are used to achieve self-healing of the organic coating.
It significantly improves the density of organic resin after curing, enhances active and long-term anti-corrosion capabilities, and extends the service life of the protected materials.
Smart Images

Figure CN119463555A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anticorrosive inorganic pigment synthesis, and in particular to a zinc phosphate-based composite pigment loaded with a nano corrosion inhibitor and a preparation method thereof. Background Art
[0002] Utilize NH4 + The method of preparing zinc ammonium phosphate pigment by doping zinc phosphate can significantly improve the hydrolysis ability of zinc phosphate salt pigments and accelerate the corrosion inhibition effect (PO4) 3- The release rate of ammonium zinc phosphate can promote the formation of a passivation film on the substrate surface; on the other hand, it can also generate OH - NH4 + Plasma forms strong coordination bonds with polar bonds in water-based coatings, thereby significantly reducing the cross-linking reaction and volume shrinkage during the curing process of organic resins and improving the density of epoxy coatings.
[0003] However, due to the volatilization of solvent water in the curing process of waterborne epoxy coatings, and the cross-linking reaction between waterborne epoxy coatings and organic resins, the volume of waterborne epoxy coatings shrinks and structural defects occur. This structural defect is difficult to completely eliminate by simply adding zinc ammonium phosphate pigments. Specifically, the volatilization of solvent water in waterborne epoxy coatings is affected by many factors, resulting in differences in the speed and degree of water volatilization in different parts of the coating. The addition of zinc ammonium phosphate pigments cannot change the nature of water volatilization being affected by environmental factors, so it is impossible to accurately control the uniform volatilization of water in the coating; in addition, due to factors such as uneven distribution of curing agents and differences in local environmental conditions (such as local temperature differences), the degree and speed of resin cross-linking in different regions are different. This uneven cross-linking reaction will cause uneven shrinkage of the coating volume, resulting in stress concentration and thus forming structural defects. Zinc ammonium phosphate pigments mainly interact with other components in the coating through their own hydrolysis and other characteristics to optimize the coating performance. It cannot directly interfere with the uniformity of the cross-linking reaction of organic resins, so it is difficult to eliminate the structural defects caused by uneven cross-linking reactions.
[0004] In addition, with the corrosive H2O, Cl - , H + Plasma continuously penetrates the epoxy coating, which, on the one hand, causes the hydrolysis of the doped pigment to form local voids, and on the other hand, releases the stress within the coating, prompting the initiation and expansion of local microcracks, which will further cause structural defects in the coating.
[0005] In other words, the current use of zinc ammonium phosphate pigments as anti-corrosion materials in water-based epoxy coatings still cannot solve the structural defects of the water-based epoxy coating layer, resulting in damage to the anti-corrosion performance of the coating during service, affecting the overall service life. Summary of the invention
[0006] The purpose of the present invention is to provide a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor and a preparation method thereof, and to load the nano-corrosion inhibitor on a zinc phosphate-based pigment with a three-dimensional structure, in order to solve the problem that a large number of pinholes, microcracks, voids and other structural defects still exist in the zinc phosphate-based pigment prepared by the existing method after being doped with an organic resin and cured, thereby improving the ability of active anti-corrosion and long-term anti-corrosion.
[0007] To achieve the above objectives, the present technical solution provides a method for preparing a zinc phosphate-based composite pigment loaded with a nano corrosion inhibitor, comprising the following steps: S1: preparing a first solution, wherein the first solution contains zinc ions and a non-ionic surfactant, and the pH value of the first solution is 1-5; S2: preparing a slow-release agent solution, wherein the slow-release agent solution contains a corrosion inhibitor metal cation, a nonionic surfactant and a complexing agent, and the pH value of the corrosion inhibitor is 1-5; S3: preparing a first mixed solution, wherein the mixed solution is obtained by mixing the corrosion inhibitor solution and the first solution; S4: preparing a second solution, wherein the second solution contains phosphate ions, phosphoric acid and an organic solvent, and the pH value of the second solution is 1-5; S5: Obtaining a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor: spraying the second solution in an atomized state into the first mixed solution to obtain a second mixed solution, placing the second mixed solution in an ultrasonic oscillation and microwave heating environment to react for a period of time, and then filtering to obtain a precipitate, and drying the precipitate to obtain a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor.
[0008] In the second aspect, the present application provides a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor, which is prepared according to a preparation method of a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor, and has a zinc phosphate base with a three-dimensional structure, and the surface of the zinc phosphate base is loaded with a nano-scale corrosion inhibitor.
[0009] Compared with the prior art, this technical solution has the following characteristics and beneficial effects: The zinc phosphate-based composite pigment loaded with nano-corrosion inhibitor prepared in this scheme successfully loads the corrosion inhibitor with self-repairing function. When added to the organic coating, through the release and migration of the inhibitor ions, the complex reaction can occur again to form a precipitate to fill the structural defects, thereby realizing the self-repair of the organic coating. This not only effectively improves the density of the organic resin after curing, but also significantly enhances the active anti-corrosion ability, enabling it to have long-term anti-corrosion in complex marine environments, greatly extending the service life of the protected materials, and providing a better solution for the field of anti-corrosion materials.
[0010] This solution carefully adjusts the components of each solution and the reaction conditions to promote the mixing reaction of the first solution and the second solution to generate zinc phosphate particles with a three-dimensional structure, and load the corrosion inhibitor ions on them. This three-dimensional zinc phosphate-based composite pigment, on the one hand, increases the stability and specific surface area of the pigment itself, allowing it to play a better role in the application; on the other hand, the three-dimensional structure provides a more favorable spatial environment for the loading of the corrosion inhibitor, which helps the corrosion inhibitor to be evenly distributed and exert its corrosion inhibition effect for a long time, further improving the anti-corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Scanning electron micrograph of the three-dimensional flower-like structured ammonium zinc phosphate composite pigment loaded with cerium ions prepared in Example 1.
[0012] Figure 2 XRD spectrum of the three-dimensional flower-like structured ammonium zinc phosphate composite pigment loaded with cerium ions prepared in Example 1.
[0013] Figure 3 Scanning electron micrograph of the three-dimensional spherical zinc phosphate composite pigment loaded with cerium ions prepared in Example 2.
[0014] Figure 4 XRD spectrum of the three-dimensional spherical zinc phosphate composite pigment loaded with cerium ions prepared in Example 2.
[0015] Figure 5 Scanning electron micrograph of the three-dimensional flower-like structured ammonium zinc phosphate composite pigment loaded with lanthanum ions prepared in Example 3. DETAILED DESCRIPTION
[0016] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0017] Those skilled in the art should understand that, in the disclosure of the present invention, the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the above terms should not be understood as limiting the present invention.
[0018] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0019] The present invention provides a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor and a preparation method thereof. The zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor loads a corrosion inhibitor with self-healing ability onto the surface of the zinc phosphate-based pigment with a three-dimensional structure, thereby further improving the density of the coating after the zinc phosphate-based composite pigment is doped with an organic resin and cured, thereby improving its active anti-corrosion ability, thereby playing an important role in the new generation of anti-corrosion materials adaptable to complex marine environments.
[0020] Specifically, the method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor provided in this scheme comprises the following steps: S1: preparing a first solution, wherein the first solution contains zinc ions and a non-ionic surfactant, and the pH value of the first solution is 1-5; S2: preparing a slow-release agent solution, wherein the slow-release agent solution contains a corrosion inhibitor metal cation, a nonionic surfactant and a complexing agent, and the pH value of the corrosion inhibitor is 1-5; S3: preparing a first mixed solution, wherein the mixed solution is obtained by mixing the corrosion inhibitor solution and the first solution; S4: configuring a second solution, wherein the second solution contains phosphate ions, phosphoric acid and an organic solvent, and the pH value of the second solution is 1 to 5; S5: Obtaining a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor: spraying the second solution in an atomized state into the first mixed solution to obtain a second mixed solution, placing the second mixed solution in an ultrasonic oscillation and microwave heating environment to react for a period of time, and then filtering to obtain a precipitate, and drying the precipitate to obtain a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor.
[0021] It should be noted that since the zinc phosphate-based composite pigment loaded with nano-corrosion inhibitor in the present scheme is loaded with a nano-corrosion inhibitor with self-repairing function, when the zinc phosphate-based composite pigment is added to the organic coating, a complex reaction can occur again through the release and migration between the release agent ions to form a poorly soluble or insoluble precipitate to fill in the structural defects, thereby achieving self-repair of the organic coating.
[0022] The first solution configured in step S1 of this scheme contains zinc ions, and the second solution configured in step S4 contains phosphate ions. This scheme adjusts the reaction conditions and reaction reagents so that the first solution and the second solution can produce zinc phosphate particles with a three-dimensional structure after mixing and reacting. At the same time, the corrosion inhibitor solution is added in step S2 to load the corrosion inhibitor ions on the zinc phosphate particles with a three-dimensional structure, thereby obtaining a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor and having a self-repairing function.
[0023] Specifically, in step S1: The zinc ions contained in the first solution come from soluble zinc salts, wherein the soluble zinc salts are selected from one or more of zinc nitrate, zinc sulfate, zinc acetate, and zinc carbonate. This is because these soluble zinc salts have good solubility, can efficiently allow zinc ions to enter the first solution, ensure the zinc ion concentration required for subsequent reactions, and these soluble zinc salts are relatively common and cost-effective, easy to obtain and use, and are conducive to large-scale implementation of the scheme.
[0024] The nonionic surfactant contained in the first solution is one or more of polyethylene glycol, polysorbate, glycerol, and pentaerythritol. The addition of nonionic surfactants can effectively inhibit the subsequent growth of zinc phosphate crystals, thereby forming nanocrystals with smaller sizes, and at the same time effectively inhibit the occurrence of nanocrystal agglomeration. In other words, this solution adds a nonionic surfactant to the first solution to accurately inhibit the growth of zinc phosphate crystals, promote the formation of finer nanocrystals, which can greatly increase the specific surface area of the product, and can also effectively inhibit the agglomeration of nanocrystals, ensuring that the nanocrystals are evenly dispersed so that each crystal can fully play its role.
[0025] The pH value of the first solution is controlled at 1-5, which has the advantage of ensuring that zinc ions or other cations are stably present in the first solution. Correspondingly, the pH value of the first solution is adjusted by adding a pH adjuster, which is one or more of nitric acid, sulfuric acid, acetic acid, citric acid, and tartaric acid.
[0026] It should be noted that, in some embodiments, the first solution contains a complexing agent, wherein the complexing agent is one or more of acetic acid, citric acid, salicylic acid, propionic acid, and tartaric acid. The reason for adding the complexing agent is to form a stable complex with the cations in the first solution, which helps to improve the stability of the cations in the first solution to prevent adverse factors such as precipitation, and can also regulate the activity of zinc ions to a certain extent, so that the zinc ions can accurately participate in the reaction process when they are subsequently mixed with other substances.
[0027] Of course, the first solution is a solution prepared in deionized water. In some embodiments, the mass ratio of the soluble zinc salt and the non-ionic surfactant in the first solution is 3:1 to 5:1.
[0028] If the first solution contains a complexing agent, the mass ratio of the soluble zinc salt, the nonionic surfactant and the complexing agent in the first solution is 3:1:1 to 5:1:1.
[0029] In addition, in some embodiments, the first solution contains a soluble ammonium salt, which provides NH4 + Ion, NH4 + Ion, Zn 2+ Ions and (PO4) 3- The ion mixing reaction forms zinc ammonium phosphate based pigment. At this time, the soluble ammonium salt is selected from one or more of ammonium nitrate, ammonium acetate, ammonium sulfate and ammonium carbonate.
[0030] Correspondingly, the mass ratio of the soluble zinc salt, the soluble ammonium salt and the non-ionic surfactant in the first solution is 3:3:1~5:5:1.
[0031] If the first solution contains a complexing agent, the mass ratio of the soluble zinc salt, the soluble ammonium salt, the nonionic surfactant and the complexing agent in the first solution is 3:3:1:1~5:5:1:1.
[0032] Specifically, the content of each component in the first solution is: in each liter of deionized water, the soluble zinc salt is 5g~30g, the soluble ammonium salt is 5g~30g, the non-ionic surfactant is 1g~10g or 5mL~20mL, the complexing agent is 1g~10g or 5mL~20mL, and the first pH adjuster is 1g~10g or 5mL~20mL.
[0033] In some embodiments, the configured first solution is placed in an auxiliary device with ultrasonic oscillation and microwave heating functions, and the ultrasonic oscillation frequency is controlled to be 20kHz to 130kHz; the microwave radiation heater power is 100W to 2000W. The 20kHz to 130kHz frequency of ultrasonic oscillation can produce a cavitation effect, promote uniform dispersion of solution components, avoid local uneven concentrations, accelerate reactions, and increase the collision frequency and energy of reactants. The 100W to 2000W power of microwave heating can heat the solution quickly and evenly, avoid temperature gradient problems, and can accurately control the temperature to control the reaction process, which will help the subsequent generation of zinc ammonium phosphate-based pigments to proceed smoothly and improve product quality and performance.
[0034] In some embodiments, the temperature of the first solution is 25°C to 50°C.
[0035] In step S2: The corrosion inhibitor metal cations in the corrosion inhibitor solution are cerium ions and / or lanthanum ions, and correspondingly, the corrosion inhibitor metal cations come from soluble cerium salts and / or soluble lanthanum salts. Cerium and lanthanum ions themselves have good corrosion inhibition properties, and soluble cerium salts or lanthanum salts can ensure that cerium and lanthanum ions are stably and evenly present in the corrosion inhibitor solution, so that when mixed with other solutions in the subsequent reaction, they can accurately participate in the process of forming a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor, thereby improving the corrosion inhibition effect of the composite pigment.
[0036] In some embodiments, the soluble cerium salt is selected from one or more of cerium nitrate, cerium sulfate, ammonium cerium sulfate, and cerium acetate. In some embodiments, the soluble lanthanum salt is selected from one or more of lanthanum nitrate, lanthanum sulfate, and lanthanum acetate.
[0037] The nonionic surfactant in the corrosion inhibitor solution comes from one or more of polyethylene glycol, polysorbate, glycerol, and pentaerythritol. This type of nonionic surfactant can effectively reduce the surface tension of the solution, allowing the corrosion inhibitor solution to spread better on the metal surface, ensuring that the corrosion inhibitor metal cations (cerium ions and / or lanthanum ions) can be more evenly covered on the metal surface, enhancing the corrosion inhibition effect, and at the same time inhibiting the agglomeration of the corrosion inhibitor components in the solution to ensure that the components are evenly dispersed.
[0038] The pH value of the corrosion inhibitor solution is adjusted by a pH adjuster to control the pH value at 1-5. The pH adjuster is one or more of nitric acid, sulfuric acid, acetic acid, citric acid, and tartaric acid. The advantage of this is that the corrosion inhibitor metal cations in the corrosion inhibitor solution can be stably present.
[0039] In some embodiments, the corrosion inhibitor solution contains a complexing agent, and the complexing agent is selected from one or more of disodium ethylenediaminetetraacetate, sodium cyclohexaneate, and sodium diethyldithiocarbamate. The complexing agent forms a stable complex with the corrosion inhibitor metal cation, which can effectively prevent the metal cation from precipitating in the solution due to various factors.
[0040] Of course, the corrosion inhibitor solution is a solution prepared in deionized water. In some embodiments, the mass ratio of the soluble cerium salt and the non-ionic surfactant in the corrosion inhibitor solution is 2:1 to 5:1. Similarly, in some embodiments, the mass ratio of the soluble lanthanum salt and the non-ionic surfactant in the corrosion inhibitor solution is 2:1 to 5:1.
[0041] If the corrosion inhibitor solution contains a complexing agent, the mass ratio of the soluble cerium salt, the nonionic surfactant and the complexing agent in the corrosion inhibitor solution is 2:1:1~5:1:1. The mass ratio of the soluble lanthanum salt, the nonionic surfactant and the complexing agent in the corrosion inhibitor solution is 2:1:1~5:1:1.
[0042] Specifically, in every liter of deionized water, the soluble cerium salt is 5g~20g, or the soluble lanthanum salt is 5g~20g, the surfactant is 1g~10g or 5mL~20mL, the complexing agent is 1g~10g or 5mL~20mL, and the pH adjuster is 1g~10g or 5mL~20mL.
[0043] In addition, it should be noted that the nonionic surfactants in the first solution and the corrosion inhibitor solution may be the same or different, and similarly, the pH adjusters may be the same or different.
[0044] In some embodiments, the volume ratio of the first solution to the corrosion inhibitor solution is 1:1 to 5:1.
[0045] Regarding step S3: The corrosion inhibitor solution and the first solution are mixed to form a first mixed solution, wherein the first mixed solution contains zinc ions and corrosion inhibitor metal cations, or the first mixed solution contains zinc ions, ammonium ions and corrosion inhibitor metal cations.
[0046] Regarding step S4: The phosphate ions contained in the second solution come from phosphoric acid and soluble phosphates, and the soluble phosphates are selected from one of sodium phosphate, ammonium phosphate, potassium phosphate, sodium hydrogen phosphate, ammonium hydrogen phosphate, potassium hydrogen phosphate, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, potassium dihydrogen phosphate, or a combination of several of them under compatible conditions.
[0047] In addition, the phosphoric acid in the second solution is selected from one or both of orthophosphoric acid and / or metaphosphoric acid. The phosphoric acid in this solution has acidity that can adjust the pH value of the second solution to a reasonable range of 1 to 5, and the phosphoric acid itself can ionize phosphate ions, which together with soluble phosphates serve as a source of phosphate ions, which helps to accurately control the concentration of phosphate ions in the solution to meet the specific requirements for the amount of phosphate ions in the reaction of forming a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor, ensuring that the reaction proceeds as expected, thereby obtaining ideal product performance.
[0048] The organic solvent contained in the second solution is one or more of ethanol, polyethylene glycol, and glycerol. The organic solvent can dissolve phosphoric acid and soluble phosphoric acid well to promote the uniform dispersion of various substances, so that when mixed with other solutions, the reactants can interact with each other in a uniform environment, which is conducive to building a regular and stable three-dimensional structural framework. In addition, the organic solvent can change the viscosity of the second solution to affect the diffusion rate of the reactants, which helps the various components to gather in an orderly manner according to a specific arrangement, gradually build up the hierarchy and network of the three-dimensional structure, and ensure that it has good connectivity and integrity.
[0049] The pH value of the second solution is adjusted by a pH regulator to control the pH value to be between 1 and 5. The pH regulator is selected from one or more of sulfuric acid, phosphoric acid, nitric acid, sodium dihydrogen phosphate, and potassium dihydrogen phosphate. The advantage of this is that it promotes the generation of phosphate ions (PO4). 3- 、Zn ion Zn 2+ and ammonium ion NH4 + Reaction and formation of precipitate.
[0050] Of course, the second solution is a solution prepared in deionized water. In some embodiments, the mass ratio of phosphoric acid, soluble phosphate and organic solvent in the second solution is 3:1:2 to 6:1:2.
[0051] Specifically, in each liter of deionized water, phosphoric acid is 0.01L~0.1L, soluble phosphate is 5g~30g, organic solvent is 10mL~50mL, and pH adjuster is 1g~10g or 5mL~20mL.
[0052] In some embodiments, the second solution is placed in a magnetically stirred water bath, and the stirring speed of the magnetically stirred water bath is 50 r·min -1 Up to 1000 r·min -1 , the heating power is 100W to 2000W to control the temperature of the second solution to 25℃~50℃.
[0053] Regarding step S5: An air compressor spray device is used to spray the second solution in an atomized state into the first mixed solution to obtain a second mixed solution, the second mixed solution is placed in an ultrasonic oscillation and microwave heating environment to react for 0.1h~1h, and then filtered to obtain a precipitate, the microwave heating temperature is controlled to be 25°C~50°C, and the precipitate is dried in a drying oven to obtain a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor, wherein the temperature of the drying oven is 50°C~200°C.
[0054] In some embodiments, the volume ratio of the second solution to the first mixed solution is 1:1 to 5:1.
[0055] This solution uses an air compressor spray device to spray the second solution in an atomized state into the first mixed solution, which can make the second solution highly dispersed into tiny droplets, greatly increasing the contact area with the first mixed solution, ensuring that the various components in the two solutions are more fully and evenly mixed, which is conducive to the rapid and accurate chemical reaction between the reactants in the subsequent reaction, and lays a good foundation for the formation of high-quality zinc phosphate-based composite pigments loaded with nano-corrosion inhibitors.
[0056] The cavitation effect produced by ultrasonic vibration can increase the collision frequency and energy between the reactant molecules, while microwave heating can heat the solution quickly and evenly. The combination of the two can significantly accelerate the chemical reaction between the various components in the solution within a reaction time of 0.1h to 1h, prompting the zinc phosphate-based composite pigment to form faster and improve production efficiency; the temperature of microwave heating is controlled at 25℃ to 50℃. This temperature range can not only provide a suitable energy environment for the reaction and promote the reaction, but also avoid problems such as decomposition of reactants or excessive side reactions due to excessive temperature, ensuring that the reaction proceeds smoothly in the direction of generating the target product.
[0057] The present invention adopts an air compressor spray device to spray the second solution into the first mixed solution in an atomized form, and simultaneously uses an ultrasonic oscillation and microwave heating auxiliary device to continuously ultrasonically refine, heat and keep warm, thereby promoting the generation of a zinc phosphate-based composite pigment loaded with a nano-level corrosion inhibitor. The zinc phosphate-based composite pigment loaded with a nano-level corrosion inhibitor prepared by the method has high solubility in aqueous solution, strong hydrolysis ability, and can form a sparingly soluble or insoluble precipitate to fill in structural defects through the release and migration of corrosion-inhibiting ions, thereby realizing the self-repairing effect of the organic coating, thereby further improving the density of the organic resin after curing, and significantly improving its active anti-corrosion and long-term anti-corrosion capabilities.
[0058] In addition, the zinc phosphate-based composite pigment loaded with nano-scale corrosion inhibitor prepared in this scheme has a zinc phosphate base with a three-dimensional structure, and the surface of the zinc phosphate base is loaded with nano-scale corrosion inhibitor.
[0059] The application team designed the following examples to verify the feasibility of the zinc phosphate-based composite pigment loaded with nano-scale corrosion inhibitor in this solution: Example 1: Ammonium zinc phosphate composite pigment based on three-dimensional flower-like structure loaded with cerium ions S1. Prepare the first solution: take a clean beaker with a capacity of 10L, add 1L of deionized water into the beaker, then add 5g of zinc acetate, 10g of ammonium acetate, 10mL of polyethylene glycol, and 10mL of acetic acid in sequence, and use ultrasonic oscillation and microwave heating auxiliary devices to ultrasonically refine and heat the L1 solution and maintain the temperature at 60°C.
[0060] S2. Prepare the corrosion inhibitor solution and the first mixed solution: take a clean beaker with a capacity of 10 L, add 1 L of deionized water into the beaker, and then add 10 g of cerium nitrate, 2 g of disodium ethylenediaminetetraacetate, and 10 mL of acetic acid solution in sequence. When the solid is completely dissolved, introduce the corrosion inhibitor solution into the first solution to form a first mixed solution.
[0061] S3. Prepare the second solution: Take a clean beaker with a capacity of 10L, add 1L of deionized water to the beaker, then add 2mL of phosphoric acid, 10g of diammonium phosphate, and 40mL of ethanol in sequence, and heat the second solution in a magnetic stirring water bath, maintain the temperature at 60℃, and stir at a speed of 200 r·min -1 .
[0062] S4. Use an air compressor spray device to spray the second solution into the first mixed solution to obtain a second mixed solution, and continue to use ultrasonic oscillation and microwave heating auxiliary devices to perform ultrasonic refinement and heating and maintain the temperature at 60°C.
[0063] S5. Filter the precipitate using a vacuum filtration device, and dry the precipitate in a drying oven, wherein the temperature of the drying oven is set to 150°C.
[0064] The scanning electron microscope image of the zinc ammonium phosphate composite pigment based on the three-dimensional flower-like structure loaded with cerium ions obtained in Example 1 is as follows: Figure 1 As shown in Figure 2, the XRD spectrum of the zinc ammonium phosphate composite pigment based on the three-dimensional flower-like structure loaded with cerium ions is as follows: Figure 2 As shown, it can be seen that cerium ions are loaded on the surface of the three-dimensional zinc ammonium phosphate composite pigment. The composite pigment not only has the three-dimensional flower-like structure, high solubility and good hydrolysis ability of zinc ammonium phosphate pigment; but also has excellent corrosion inhibition performance and self-healing ability, thereby significantly improving the density of the organic resin after curing and enhancing its active anti-corrosion and long-term anti-corrosion capabilities.
[0065] Example 2 A zinc phosphate composite pigment based on a three-dimensional spherical structure loaded with cerium ions S1. Prepare the first solution: take a clean beaker with a capacity of 10 L, add 1 L of deionized water into the beaker, then add 5 g of zinc nitrate and 5 mL of polyethylene glycol in sequence, use ultrasonic oscillation and microwave heating auxiliary equipment to perform ultrasonic refinement, heating and maintain the temperature at 25°C.
[0066] S2. Prepare the corrosion inhibitor solution and the first mixed solution: Take a clean beaker with a capacity of 10L, add 1L of deionized water to the beaker, and then add 15g of cerium nitrate, 2g of disodium ethylenediaminetetraacetate, and 2mL of nitric acid solution in sequence. When the solid is completely dissolved, introduce the slow-release agent solution into the first solution to form a first mixed solution.
[0067] S3. Prepare the second solution: take a clean beaker with a capacity of 10L, add 1L of deionized water into the beaker, then add 10mL of phosphoric acid and 50mL of ethanol in sequence, heat in a magnetic stirring water bath, maintain the temperature at 25°C, and stir at a speed of 200 r·min-1.
[0068] S4. Use an air compressor spray device to spray the second solution into the first mixed solution to form a second mixed solution, and continue to use ultrasonic oscillation and microwave heating auxiliary devices to perform ultrasonic refinement and heating and maintain the temperature at 25°C.
[0069] S5. Filter the precipitate using a vacuum filtration device, and dry the precipitate in a drying oven, wherein the temperature of the drying oven is set to 150°C.
[0070] The scanning electron microscope image of the zinc ammonium phosphate composite pigment based on the three-dimensional spherical structure loaded with cerium ions obtained in Example 1 is as follows: Figure 3 As shown, the XRD spectrum of the zinc ammonium phosphate composite pigment based on the three-dimensional spherical structure loaded with cerium ions is as follows Figure 4 As shown, it can be seen that Example 2 of the present invention adopts the method assisted by ultrasonic vibration and microwave heating to synthesize a three-dimensional spherical zinc phosphate composite pigment loaded with cerium ions. The composite pigment not only has the three-dimensional flower-like structure and good physical shielding properties of zinc phosphate pigment; but also has excellent corrosion inhibition efficiency and self-repairing ability, thereby significantly improving the density of the organic resin after curing and enhancing its active anti-corrosion and long-term anti-corrosion capabilities.
[0071] Example 3: Ammonium zinc phosphate composite pigment based on three-dimensional flower-like structure loaded with lanthanum ions S1. Prepare the first solution: take a clean beaker with a capacity of 10L, add 1L of deionized water into the beaker, then add 5g of zinc acetate, 10g of ammonium acetate, 10mL of polyethylene glycol, and 10mL of acetic acid in sequence, and use ultrasonic oscillation and microwave heating auxiliary devices to ultrasonically refine and heat the L1 solution and maintain the temperature at 60°C.
[0072] S2. Prepare the corrosion inhibitor solution and the first mixed solution: take a clean beaker with a capacity of 10 L, add 1 L of deionized water into the beaker, and then add 10 g of lanthanum nitrate, 2 g of disodium ethylenediaminetetraacetate, and 10 mL of acetic acid solution in sequence. When the solid is completely dissolved, introduce the corrosion inhibitor solution into the first solution to form a first mixed solution.
[0073] S3. Prepare the second solution: Take a clean beaker with a capacity of 10L, add 1L of deionized water to the beaker, then add 2mL of phosphoric acid, 10g of diammonium phosphate, and 40mL of ethanol in sequence, and heat the second solution in a magnetic stirring water bath, maintain the temperature at 60℃, and stir at a speed of 200 r·min -1 .
[0074] S4. Use an air compressor spray device to spray the second solution into the first mixed solution to obtain a second mixed solution, and continue to use ultrasonic oscillation and microwave heating auxiliary devices to perform ultrasonic refinement and heating and maintain the temperature at 60°C.
[0075] S5. Filter the precipitate using a vacuum filtration device, and dry the precipitate in a drying oven, wherein the temperature of the drying oven is set to 150°C.
[0076] The scanning electron microscope image of the zinc ammonium phosphate composite pigment based on the three-dimensional flower-like structure loaded with lanthanum ions obtained in Example 3 is as follows: Figure 5 As shown, it can be seen that lanthanum ions are loaded on the surface of the three-dimensional zinc ammonium phosphate composite pigment. The composite pigment not only has the three-dimensional flower-like structure, high solubility and good hydrolysis ability of zinc ammonium phosphate pigment; but also has excellent corrosion inhibition performance and self-healing ability, thereby significantly improving the density of the organic resin after curing and enhancing its active anti-corrosion and long-term anti-corrosion capabilities.
[0077] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. A method for preparing a zinc phosphate-based composite pigment loaded with a nano corrosion inhibitor, characterized in that: The following steps are involved: S1: preparing a first solution, wherein the first solution contains zinc ions and a non-ionic surfactant, and the pH value of the first solution is 1-5; S2: preparing a slow-release agent solution, wherein the slow-release agent solution contains a corrosion inhibitor metal cation, a nonionic surfactant and a complexing agent, and the pH value of the corrosion inhibitor is 1-5; S3: preparing a first mixed solution, wherein the mixed solution is obtained by mixing the corrosion inhibitor solution and the first solution; S4: preparing a second solution, wherein the second solution contains phosphate ions, phosphoric acid and an organic solvent, and the pH value of the second solution is 1-5; S5: Obtaining a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor: spraying the second solution in an atomized state into the first mixed solution to obtain a second mixed solution, placing the second mixed solution in an ultrasonic oscillation and microwave heating environment to react for a period of time, and then filtering to obtain a precipitate, and drying the precipitate to obtain a zinc phosphate-based composite pigment loaded with a nano-corrosion inhibitor.
2. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The nonionic surfactant contained in the first solution and the corrosion inhibitor solution is one or more of polyethylene glycol, polysorbate, glycerol and pentaerythritol.
3. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The pH values of the first solution and the corrosion inhibitor solution are adjusted by adding a pH adjuster, wherein the pH adjuster is one or more of nitric acid, sulfuric acid, acetic acid, citric acid, and tartaric acid.
4. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The first solution contains a complexing agent, wherein the complexing agent is one or more of acetic acid, citric acid, salicylic acid, propionic acid and tartaric acid.
5. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The temperature of the first solution and the second solution is 25°C to 50°C.
6. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The corrosion inhibitor metal cation is cerium ion and / or lanthanum ion, and the corrosion inhibitor metal cation comes from soluble cerium salt and / or soluble lanthanum salt.
7. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The corrosion inhibitor solution contains a complexing agent, and the complexing agent is selected from one or more of disodium ethylenediaminetetraacetate, sodium cyclohexaneate, and sodium diethyldithiocarbamate.
8. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The phosphoric acid in the second solution is selected from one or both of orthophosphoric acid and / or metaphosphoric acid, and the organic solvent is selected from one or more of ethanol, polyethylene glycol, and glycerol.
9. The method for preparing the zinc phosphate-based composite pigment loaded with nano corrosion inhibitor according to claim 1, characterized in that: The pH value in the second solution is adjusted by a pH adjuster, and the pH adjuster is selected from one or more of sulfuric acid, phosphoric acid, nitric acid, sodium dihydrogen phosphate, potassium dihydrogen phosphate, and ammonia water.
10. A zinc phosphate-based composite pigment loaded with a nano corrosion inhibitor, characterized in that: According to the preparation method of the zinc phosphate-based composite pigment loaded with nano-corrosion inhibitor according to any one of claims 1 to 9, a zinc phosphate base having a three-dimensional structure is prepared, and the surface of the zinc phosphate base is loaded with a nano-scale corrosion inhibitor.
Citation Information
Patent Citations
Anti-corrosion cerium-modified zinc phosphate decorated graphene oxide nanoplatform
CA3259223A1
Special anti-rust phosphate pigment for waterborne coating and preparation method of pigment
CN105542538A
Anticorrosive paint and preparation method thereof
CN106280750A
Pigment grade corrosion inhibitor host-guest compositions and procedure
WO2005003408A2
Anti-corrosion cerium-modified zinc phosphate decorated graphene oxide nanoplatform
WO2023240347A1